Animal welfare issues in capture-based aquaculture - Chandararathna, Uthpala; Iversen, Martin Haugmo; Korsnes, Kjetil; Sørensen, Mette; Vatsos, Ioannis (Animals, 2021)
Capture-based aquaculture (CBA) represents a type of intensive aquaculture production system for some economically valuable fish species, such as bluefin tuna (Thunnus thynnus), eel (Anguilla spp.) and Atlantic cod (Gadus morhua). In CBA, fish are captured from the wild in certain periods of the year, and following a recovery phase, they are kept in rearing facilities for a period of time, until they reach the market size. In this case, the fish are wild and have not gone through domestication like other fish species that are reproduced and farmed under the established farming systems. Therefore, these fish are not genetically adapted to live under the intensive farming conditions, and thus their welfare may be compromised in different manners compared to their domesticated counterparts. This review presents an overview of the current situation of CBA, while focusing on the assessment of fish welfare in CBA. The most commonly used fish welfare indicators will be discussed in relation to the different stages of CBA. publishedVersion